NOVEL SPECTROPHOTOMETRIC METHODS FOR THE QUANTIFICATION OF DESVENLAFAXINE IN PURE AND PHARMACEUTICAL DOSAGE FORM - Sreeja U,; Gurupadayya Bm,; Chandan Rs, (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: Two simple, sensitive and economic spectrophotometric methods are developed for the determination of desvenlafaxine in pure and its pharmaceutical formulations. Methods: The developed methods are based upon the reaction of oxidative coupling of desvenlafaxine with 3-methyl-2-benzthiazolinonehydrazone (MBTH) (Method A) and 2, 2' bipyridyl (Method B) in the presence of ferric chloride. The colored complex produced was measured at 663 nm, 522 nm for method A and B respectively against the reagent blank. The optimum experimental parameters for the color productions are selected. Results: Beer's law is valid within a concentration range of 20-100 μg/ml and 5-25 μg/ml and for method A, B respectively. The percentage recoveries were found in the range of 99.47±0.1789 for method A and 100.08±0.144 for method B. The limit of detection and limit of quantification were found to be 0.825 μg/ml and 2.5 μg/ml respectively for method A and 0.1061 μg/ml and 0.321 μg/ml for method B respectively. Conclusion: The developed methods are applied for the determination of desvenlafaxine in bulk and its pharmaceutical formulations without any interference from excipients. Keywords: Spectrophotometric, Desvenlafaxine, Oxidative coupling, 3-methyl-2-benzthiazolinone hydrazone, 2, 2- bipyridyl, FeCl3.